The other Gujarat - Shinoda, Takashi (Mumbai : Popular Prakashan, 2002)
Contributed articles with reference to social change among weaker sections in Gujarat, India
Library has 2 copies.
Keywords: Social Change -- India -- Gujarat; Marginality, Social -- India -- Gujarat; Gujarat (India) -- Social conditions; Gujarat (India) -- Economic conditions